Health Services for Marginalized Groups: A Sociological Study on Construction Workers in Paccerakkang, Makassar City - Andi Alim; Arlin Adam; Asriani Minarti; Adhyatma. A; Muhammad Syafri; Abdul Gafur; Riswan Marsal (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: This study aims to gain an in-depth understanding of the experiences of construction workers in accessing health services in Paccerakkang Subdistrict, Biringkanaya District, Makassar City. As part of the informal sector workforce, construction workers face various health risks as well as structural limitations in obtaining adequate health services. This study adopts a health sociology perspective to examine how social, economic, and public policy factors influence access to health services among informal workers. Methods: This study employed a qualitative approach with a phenomenological design. The research participants consisted of six construction workers selected purposively based on the criteria of being aged 18–60 years, actively working as construction workers, and having experience in accessing health services within the past year. Data were collected through in-depth interviews, participant observation in the workers’ work and residential environments, and documentation to strengthen the empirical context of the study. Data analysis was conducted using thematic analysis through processes of data reduction, categorisation, and meaning-making to identify patterns of experience and the participants’ interpretations of access to health services. Results: The findings indicate that construction workers perceive health services not only as a means of medical treatment but also as a form of social protection that helps maintain work productivity and family well-being. The main barriers to accessing health services include economic constraints, unstable income, long working hours, and the lack of occupational safety facilities. Some participants also highlighted complicated administrative procedures and high treatment costs, although in general they did not experience discrimination from health professionals. To overcome these barriers, construction workers developed adaptive strategies such as utilising formal health services and traditional treatment, maintaining health through healthy lifestyles, and relying on social support from family members and co-workers. Conclusion: This study concludes that the experiences of construction workers in accessing health services are shaped by the interaction of economic, social, occupational, and health policy factors. Therefore, stronger synergy between government institutions, health service providers, and worker communities is required to create a health service system that is more equitable, inclusive, and responsive to the needs of informal sector workers in urban settings.